<span>LJK = KJM
-10x +3 = -x + 21
-10x + x = 21 - 3
-9x = 18
x = -2
KJM = -x + 21 = 2 + 21 = 23
LJM = LJK + KJM
LJM = 23 + 23
LJM = 46º..
i think thats how its done </span>
Answer:
2ax − 6ay + bx − 3
Step-by-step explanation:
The expression is not factorable with rational numbers
Answer:
.31
Step-by-step explanation:
155 / 5 31/100
500/ 5
31÷100
Long Division for 31 divided by 100
round to a Max of 3 Decimal gives us
=0.31
The sum of the given expression expressed as a quadratic equation is 10x^2 + 13x + 11
<h3>Sum of expressions</h3>
Expressions are equations separated by mathematical signs. This expressions are known to contains certain unknowns
Given the following expression
10x^2 +7x+6 and 6x + 5
We are to take the sum of both expression to have:
f(x) = 10x^2 +7x+6 + 6x + 5
Collect the like terms
f(x) = 10x^2 + 7x + 6x + 6 + 5
f(x) = 10x^2 + 13x + 11
Hence the sum of the given expression expressed as a quadratic equation is 10x^2 + 13x + 11
Learn more on sum of functions here: brainly.com/question/11602229
#SPJ1
I answer is B your welcome.